Figure 1 from: Stur E, Borkent A (2014) When DNA barcoding and morphology mesh: Ceratopogonidae diversity in Finnmark, Norway. ZooKeys 463: 95-131. https://doi.org/10.3897/zookeys.463.7964 - Stur, Elisabeth; Borkent, Art (Zenodo, 2014)
Figure 1 - Sample sites for Ceratopogonidae in Finnmark, Norway, in 2010. Modified after Fig. 2 in Ekrem et al. (2012). Map by Marc Daverdin, NTNU University Museum.